Global stability of nonlinear feedback systems with fractional positive linear parts - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The global (absolute) stability of nonlinear systems with fractional positive and not necessarily asymptotically stable linear parts and feedbacks is addressed.
Keywords: global; stability; fractional; nonlinear; feedback; positive; system